2024
DOI: 10.1111/cts.13710
|View full text |Cite
|
Sign up to set email alerts
|

Fetal spina bifida associates with dysregulation in nutrient‐sensitive placental gene networks: Findings from a matched case–control study

Marina White,
Jayden Arif‐Pardy,
Tim Van Mieghem
et al.

Abstract: To improve outcomes in fetuses with spina bifida (SB), better understanding is needed of the molecular drivers of SB and its comorbidities. Pregnant people carrying a fetus with isolated SB (cases; n=12) or a fetus with no congenital anomalies (controls; n=21) were recruited at Mount Sinai Hospital, Toronto. Clinical data and placental samples were collected. Placental transcriptome was sequenced (Clariom DTM microarray) and a nutrient‐focused gene expression analysis pipeline was applied to determine whether … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 55 publications
(104 reference statements)
1
6
0
Order By: Relevance
“…However, it is likely that the SB cases in our cohort were not folateresponsive NTDs, given that folate deficiency is rare in the region the study took place 36 and that all mothers in the cohort were taking prenatal vitamins. 21 The lack of differences in folate transporter immunolabeling that we report is consistent with transcript-level data for expression of FRα, PCFT, and RFC that we have previously reported for this cohort. 21 It is possible that the suboptimal growth observed in ∼50% of the cases in this cohort was, in part, driven by dysfunction in other nutrient-related placental processes, such as lipid metabolism and amino acid transport, 21 and this is an area requiring further study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, it is likely that the SB cases in our cohort were not folateresponsive NTDs, given that folate deficiency is rare in the region the study took place 36 and that all mothers in the cohort were taking prenatal vitamins. 21 The lack of differences in folate transporter immunolabeling that we report is consistent with transcript-level data for expression of FRα, PCFT, and RFC that we have previously reported for this cohort. 21 It is possible that the suboptimal growth observed in ∼50% of the cases in this cohort was, in part, driven by dysfunction in other nutrient-related placental processes, such as lipid metabolism and amino acid transport, 21 and this is an area requiring further study.…”
Section: Discussionsupporting
confidence: 92%
“…Further, we previously reported that cases in this cohort had upregulated expression of five genes known to be expressed by HBCs, including genes involved in inflammatory response regulation, which is consistent with an overall enhancement of HBC function in cases. 21 Given that HBCs regulate placental angiogenesis, and changes in HBC number or polarization may alter angiogenesis, 33 an altered HBC phenotype may contribute to placental villous maldevelopment observed in these cases. 17 Future studies should consider a deeper phenotyping of the role of regulatory (M2) HBC subtypes (M2a, M2b, M2c, and M2d 38 ) in placental physiology in both healthy fetuses, and those with isolated SB, to better delineate how HBC composition may relate to placental villous maldevelopment in fetuses with isolated NTDs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations